Pengaruh Anggaran Berbasis Kinerja terhadap Kinerja Aparatur Pemerintah Daerah (Studi Kasus pada Dinas Sosial Provinsi Jawa Barat) - Febrina Astria Verasvera (Universitas Kristen Maranatha, 2016)
This research was conducted at Dinas Sosial of West Java Province, located on Jalan Raya Cibabat No. 331 Cimahi, West Java. This research tries to analyze whether there is influence of budget based on performance toward the improvement of local government officials performance. The variable X researchindicators (Budgeting Based on Performance), they are: preparation, ratification, implementation, evaluation and reporting. While for the variable Y (Performance ofLocal Government Apparatus) these are: effectiveness, efficiency, employee growth, and customer satisfaction. The method used in this research is descriptive analysismethod with a case study approach, and hypothesis testing used Rank Spearman correlation analysis in order to find out the correlation variable X (Budgeting based on Performance) and Variable Y (Performance of Local Government Apparatus).Whereas for knowing how much the influence of variable X toward variable Y, by using the coefficient of determination. Based on the results of research for the data obtained, it can be concluded that, budgeting based on performance has significanteffect on the performance of local government apparatus in the Dinas Sosial of West Java Province. It is shown in the results of Spearman Rank correlation of rs = 0.6956 and the interval from 0.60 ― 0.79 which shows a strong association level, as wellas the results of testing the hypothesis that the results show that thitung 7.1150> ttabel 1 .6707. That matter make an indication of rejection of Ho which indicates that thereis a positive relationship between the variables X with variables Y and for the coefficient of determination that shows the much influence of budgeting based on performance toward the performance of local government apparatus which obtainedyield is 48.39% while 51.61% influenced by other factors. So that expected that all officials in the Dinas Sosial able to implement the budgeting based on performance more better.Keywords: budget, performance.